2017
DOI: 10.3168/jds.2016-12133
|View full text |Cite
|
Sign up to set email alerts
|

Influence of food deprivation on intravenous glucose tolerance test traits in Holstein Friesian heifers

Abstract: Glucose is essential for numerous cellular functions due to its involvement in energy supply from early development to adulthood. In the lactating cow, glucose demands by the mammary gland significantly increase to support milk production when compared with other tissues. Thus, insufficient blood glucose levels might predispose dairy cows to metabolic disturbances. The intravenous glucose tolerance test (ivGTT) is a suitable tool to characterize glucose metabolism and insulin responses, but results must be rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 55 publications
1
6
0
Order By: Relevance
“…From all ivGTT traits assessed, only GMAX was influenced by BW, which could be related to higher glucose amounts applied as weight increased. The lack of influence of BW on ivGTT traits and insulin responses is in agreement with our previous study on fasting times (González-Grajales et al, 2017). Other studies found an association between degree of obesity and insulin maximum responses (McCann and Reimers, 1986).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…From all ivGTT traits assessed, only GMAX was influenced by BW, which could be related to higher glucose amounts applied as weight increased. The lack of influence of BW on ivGTT traits and insulin responses is in agreement with our previous study on fasting times (González-Grajales et al, 2017). Other studies found an association between degree of obesity and insulin maximum responses (McCann and Reimers, 1986).…”
Section: Discussionsupporting
confidence: 93%
“…Individual factors influencing a metabolic response (e.g., age, breed, and physiological status) should be carefully revised to obtain reliable results (Kaneko, 1997). Additionally, the effects of fasting (González-Grajales et al, 2017), stress, and diet composition on ivGTT traits in Holstein heifers have also been investigated (Görner, 2011). Surprisingly, little attention has been paid to the effects of glucose dose on ivGTT despite its wide implementation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, test standardization is important to obtain repeatable and reliable data. We have reported about test standardization including fasting times (González-Grajales et al, 2017), glucose dose (González-Grajales et al, 2018), and management and nutritional measures (Görner, 2011). However, test repeatability in young Holstein-Friesian cattle is unknown.…”
Section: Short Communicationmentioning
confidence: 99%
“…The information obtained from these responses is routinely used to assess conditions such as insulin resistance [11], diagnose diabetes, although its incidence in cattle is very low [12], determine the impact of certain compounds on insulin sensitivity [13] among other applications. Despite the wide implementation of ivGTT in cattle, careful data interpretation is always recommended because test standardization is lacking [14]. Recently, the effects of food deprivation times [14] and glucose dose [15] on ivGTT and insulin traits have been demonstrated.…”
Section: Introductionmentioning
confidence: 99%